Painful musculosceletal disorders and depression among working aged migraineurs. (14th March 2018) - Sumelahti, M.‐L.; Mattila, K.; Sumanen, M.
Abstract : Objective: Musculoskeletal disorders and depression are common among migraineurs. The aim of our study was to evaluate the occurrence of these disorders among working aged migraineurs. Material and Methods: The risk for fibromyalgia, rheumatoid arthritis (RA), osteoarthrosis (OA), sciatic syndrome, and the occurrence of depression was studied among cases who reported about these conditions and migraine in working aged Finnish population in The Health and Social Support Study (HeSSup) based on postal questionnaire in 2012. Group differences were tested by chi‐square test. Odds ratios (ORs with 95% CI) adjusted for age, gender, education level and depression were calculated with logistic regression analysis. Results: Total of 1505 migraineurs (13%) and 8092 controls were included among the 11 596 responders in 2012. Age and gender adjusted ORs, 2.37 (95% CI 1.81‐3.09) for fibromyalgia, 1.46 (1.10‐1.95) for RA, 1.58 (1.38‐1.80) for OA, and 2.09 (1.84‐2.37) for sciatic syndrome, were significant. At least moderate depression was more common among migraineurs (7.3%) than among controls (3.4%) ( P  <   .001). Conclusion: Recognition of comorbid musculoskeletal disorders and mood disorders among migraineurs needs targeted outreach in working aged population. The acute and preventive treatments to control for neuronal sensitization in migraine and comorbid pain disorders may benefit of individual treatment plan and tailored use of antidepressants.